Bilateral duplex kidney and ureter with multiple stones: a case report - Guoqing Liu; Xin Zhang; Xinyuan Yu; Junjie Chen; ZhaoRong Xu; Xiao Li (BMC Urology)
Abstract Background Bilateral duplicated kidney and ureter is a rare condition in urology, and it is even rarer for patients to have multiple stones simultaneously. We delineate the diagnostic and therapeutic trajectory of a patient presenting with bilateral duplex kidneys and ureters, characterized by the presence of multiple stones. Notably, the left kidney is a complete duplication, whereas the right kidney exhibits an incomplete duplication. Case presentation A 47-year-old male patient was diagnosed with bilateral duplex kidney and ureter combined with multiple stones. Ureteral flexible lithotripsy and percutaneous nephrolithotomy were performed successively in our hospital. On the postoperative five day, he was discharged from the hospital without apparent discomfort.The double J tube was pulled out one month later, and no stone recurrence was found after 3 months of follow-up. Conclusions Bilateral duplicated renal ureteral malformations combined with multiple stones are very rare. Stones can be removed by ureteroscopic lithotripsy or percutaneous nephrolithotripsy and sometimes multiple procedures are required, which should be chosen according to the patient’s relevant condition.